Automated vulnerability detection system based on commit messages - Wan, Liuyang (2019)
Vulnerabilities in Open Source Software (OSS) are the major culprits of cyber-attacks and security breaches today. To avoid repetitive development and speed up release cycle, software teams nowadays are increasingly relying on OSS. However, many OSS users are unaware of the vulnerable components they are using. Sometimes it will take weeks or even months for a Common Vulnerabilities and Exposures (CVE) to be determined and finally patched. Thus, to mitigate against cyber-attacks, it is important to understand both known CVEs and unknown vulnerabilities. In this thesis, we first conducted a large-scale crawling of Git commits for some popular open source repositories like Linux. Second, because there is no prior dataset for security-relevant Git commits, we developed a web-based triage system for security researchers to perform manual labelling of the commits. Finally, after the commits are cleaned and labelled, a deep neural network is implemented to automatically identify vulnerability-fixing commits (VFC) based on the commit messages. The approach has achieved significant better precision than state-of-the-art while improving the recall rate by 16.8%. In the end, we present a thorough quantitative and qualitative analysis of the results and discuss the lessons learned and room for future work.